Tradeoffs associated with autotomy and regeneration and their potential role in the evolution of regenerative abilities. (21st February 2022) - Prestholdt, Tara; White-Toney, Tai; Bates, Katie; Termulo, Kara; Reid, Sawyer; Kennedy, Katy; Turley, Zach; Steed, Clayton; Kain, Ryan; Ortman, Matt; Luethke, Tim; Degerstedt, Spencer; et al.
Abstract: The capacity of certain animals to regrow a lost appendage has been exploited as a powerful tool to study development. As a result, we now understand many of the proximate details of the regeneration process. Ironically, despite being one of the oldest studied developmental phenomena, regeneration is not often considered in the context of natural selection and evolution. Why do select species retain the capacity to shed and regrow body parts, whereas more derived lineages do not? We conducted a comprehensive study on the costs and benefits of autotomy and regeneration on Hemigrapsus nudus, the purple shore crab. In the realms of feeding and locomotion, regeneration restored fitness to what it otherwise would have been; autotomized animals showed decreases in feeding and locomotion, but regenerated animals performed no differently than intact crabs. However, for fecundity and male–male competition, regenerated animals had the lowest fitness compared with control and autotomized crabs. Our results raise the intriguing possibility that tradeoffs associated with reproduction may have led to the loss of regenerative abilities in derived lineages such as mammals and birds. Future work on the hundreds of species that regenerate lost body parts will reveal if and how this hypothesis can address the pervasive speculation plaguing the ultimate causes of regenerative losses. Abstract : Many animals have the ability to lose and regenerate body parts. Interestingly, most of those animals are relatively primitive such as worms, jellyfish, crabs, and starfish; derived animals like birds and mammals are incapable of losing and regenerating appendages. Why would evolution favor the loss of such a seemingly beneficial trait? Our research hints at the intriguing possibility that birds and mammals may have traded their relatively elaborate reproduction for their ability to regrow body parts.